2014
DOI: 10.1016/j.medici.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms and eating behavior among morbidly obese patients undergoing Roux-en-Y gastric bypass

Abstract: In morbidly obese patients endoscopic findings correlate well with gastrointestinal complain. RYGB significantly improves gastrointestinal complains and eating behavior one year postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 27 publications
1
42
3
Order By: Relevance
“…Two ‘good’‐rated studies found significant decreases in emotional eating between presurgery and 1 year , and from presurgery to 6 weeks, 1 year and 2 years, with RYGB patients reporting significantly more emotional eating than non‐obese reference subjects before but not after surgery . These positive results were supported by ‘fair’ studies that showed significant decreases in emotional eating at 1 year and 6 months and 1 year (no change from 6 to 12 months) , a significant change over time to 1 year (assessment at 3 days, 2 months and 1 year) , and significant changes over time in anxiety‐related, anger‐related and depression‐related emotional eating between presurgery and 6 months, with a decrease presurgery to 1–3 weeks and no change 1–3 weeks to 6 months .…”
Section: Resultsmentioning
confidence: 92%
“…Two ‘good’‐rated studies found significant decreases in emotional eating between presurgery and 1 year , and from presurgery to 6 weeks, 1 year and 2 years, with RYGB patients reporting significantly more emotional eating than non‐obese reference subjects before but not after surgery . These positive results were supported by ‘fair’ studies that showed significant decreases in emotional eating at 1 year and 6 months and 1 year (no change from 6 to 12 months) , a significant change over time to 1 year (assessment at 3 days, 2 months and 1 year) , and significant changes over time in anxiety‐related, anger‐related and depression‐related emotional eating between presurgery and 6 months, with a decrease presurgery to 1–3 weeks and no change 1–3 weeks to 6 months .…”
Section: Resultsmentioning
confidence: 92%
“…Overconsumption of energy-dense food postoperatively has also been associated with WR [14]. Eating behavior (including restrained, disinhibited, external, and emotional eating, and hunger perception) have shown to improve after GB [15, 16], and some studies suggest that preoperative scores may predict weight loss outcomes [12, 17]. Additionally, health-related QoL improves in most patients after bariatric surgery, but poor weight loss outcome, along with postoperative depression, can influence QoL negatively [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of diarrhea in a preoperative bariatric population is around 8%[20], being twice as high as in lean people. A possible reason for this might be a higher intake of poorly absorbed sugars[21].…”
Section: Bowel Habit Changes After Bariatric Surgerymentioning
confidence: 99%
“…Up to 75% of patients suffer from alterations of bowel habits and faecal transit time after RYGB[20]. Diarrhea is a common symptom after RYGB[6,20,24], and usual after BPD[14,25].…”
Section: Bowel Habit Changes After Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation